The Social Enterprise Ecosystem in England: An Increasingly ‘Private-Macro’ Social Economy Distorted by Policy - Hazenberg, Richard; Bajwa-Patel, Meanu (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2021)
Prior research exploring European social enterprise ecosystems identified four main ecosystem types: Statist-macro; Statist-micro; Private-macro; and Private‑micro. This paper seeks to explore the English ecosystem’s development into an increasingly Private‑macro type, focused on decreasing pluralism and increasing marketisation. The paper applies Weberian views of power, to argue that dominant stakeholders utilise their networks to create a dominant discourse that extends the Private-macro ecosystem type in England. The research utilises data gathered from 23 participants (stakeholders from the social enterprise ecosystem) in the form of semi-structured interviews and focus groups. The results demonstrate the ongoing neoliberal marketisation of the English ecosystem.